2022
DOI: 10.3390/insects13030238
|View full text |Cite
|
Sign up to set email alerts
|

Non-Native Non-Apis Bees Are More Abundant on Non-Native Versus Native Flowering Woody Landscape Plants

Abstract: Urban ecosystems can support diverse communities of wild native bees. Because bloom times are conserved by geographic origin, incorporating some non-invasive non-native plants in urban landscapes can extend the flowering season and help support bees and other pollinators during periods when floral resources from native plants are limiting. A caveat, though, is the possibility that non-native plants might disproportionately host non-native, potentially invasive bee species. We tested that hypothesis by identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In its native range, O. taurus has been classified as a polylectic species with a preference for pollen from the Juglandaceae, Rosaceae, and Fabaceae families, which is similar but broader than the pollen preferences of O. cornifrons that prefers pollen from the Rosaceae and Fabaceae families (Maeta 1978, Haider et al 2014, Vaudo et al 2020). In North America, O. taurus has been observed visiting Cercis canadensis , the eastern redbud (Fabales: Fabaceae), and several species in the genus Prunus (Rosales: Rosaceae) (Potter and Mach 2022). However, O. taurus seems to collect pollen primarily from non-native shrubs species of the genera Aesculus (Sapindales: Sapindaceae), Viburnum (Dipsacales: Adoxaceae), and Ilex (Aquifoliales: Aquifoliaceae) (Potter and Mach 2022).…”
Section: Nesting Biology Life Cycle Floral Preferences and Natural En...mentioning
confidence: 99%
See 2 more Smart Citations
“…In its native range, O. taurus has been classified as a polylectic species with a preference for pollen from the Juglandaceae, Rosaceae, and Fabaceae families, which is similar but broader than the pollen preferences of O. cornifrons that prefers pollen from the Rosaceae and Fabaceae families (Maeta 1978, Haider et al 2014, Vaudo et al 2020). In North America, O. taurus has been observed visiting Cercis canadensis , the eastern redbud (Fabales: Fabaceae), and several species in the genus Prunus (Rosales: Rosaceae) (Potter and Mach 2022). However, O. taurus seems to collect pollen primarily from non-native shrubs species of the genera Aesculus (Sapindales: Sapindaceae), Viburnum (Dipsacales: Adoxaceae), and Ilex (Aquifoliales: Aquifoliaceae) (Potter and Mach 2022).…”
Section: Nesting Biology Life Cycle Floral Preferences and Natural En...mentioning
confidence: 99%
“…In North America, O. taurus has been observed visiting Cercis canadensis , the eastern redbud (Fabales: Fabaceae), and several species in the genus Prunus (Rosales: Rosaceae) (Potter and Mach 2022). However, O. taurus seems to collect pollen primarily from non-native shrubs species of the genera Aesculus (Sapindales: Sapindaceae), Viburnum (Dipsacales: Adoxaceae), and Ilex (Aquifoliales: Aquifoliaceae) (Potter and Mach 2022). This pattern of preference for non-native plants has also been reported for O. cornifrons (Vaudo et al 2020).…”
Section: Nesting Biology Life Cycle Floral Preferences and Natural En...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regionally appropriate plant lists of trees, shrubs and flowers that attract and support pollinators are good resources to consult for landscape design or renovation (e.g., Harris et al, 2016;Braman et al, 2017;Braman and Quick, 2018;Mach and Potter, 2018;Smitley et al, 2019). Non-native, non-Apis bees were determined to be significantly more abundant visitors to nonnative vs. native plants, especially Osmia taurus Smith and Megachile sculpturalis (Smith) (Potter and Mach, 2022). Those offers suggested that planting of favored non-native hosts could have the unintended consequence of facilitating the spread of non-native, non-Apis bees in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive species can dramatically impact native communities [ 44 , 45 ], and the extent of invasion can vary significantly [ 46 , 47 ]. Invasion in this context is especially relevant with regard to disturbance [ 48 ] and the formation of novel ecosystems [ 47 ]; the common origin of non-native species can influence their behavior in a new community [ 49 ].…”
Section: Introductionmentioning
confidence: 99%